Черты политической культуры: Восточная Европа и Латинская Америка (сравнительный анализ) - Майстренко, И. (Социология: теория, методы, маркетинг, 2004)
The author uses comparative analysis for determination of similar and different features of political systems in Eastern Europe and Latin America. Latin American Way was considered to be a standard in resolution of crises by a deal of elite (the so called transition models). That is why the comparative basis was formed of leading Latin American countries and Eastern Europe which prospects are often seen as developed according to the Latin American model. By comparing both transitions from authoritarian power to democracy, typical for these countries, one can see regional features in Eastern Europe, like avalanche character and total fragmentation of political system, and cyclic democratization in Latin America. This method makes it possible to describe transitional processes without leaving the field of political analysis and asking for external reasons in order to explain nationally specific differences.